2015
DOI: 10.1007/s10653-015-9732-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of lead isotopic methods to the study of the anthropogenic lead provenance in Spanish overbank floodplain deposits

Abstract: Changes in the principal sources of Pb in overbank sediment profiles have been documented for two Spanish areas by using Pb isotopes and Pb concentrations. These locations (Madrid and Tinto-Odiel basin) represent two of the most contaminated regions in Spain. The Community of Madrid is characterized by heavy industrial and urban activity, focused mainly in Madrid City. The Tinto-Odiel basin drains the Iberian Pyrite Belt, which hosts many polymetallic massive sulphides and is heavily affected by mining activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…a common predominant Pb origin (s) for all the samples (see Table 4). Therefore, average values were used to establish comparisons with possible sources; in this regard, Adánez et al (2015) have recently reported Pb isotopic ratios in samples of the Odiel-Tinto basin in the SW of Spain that are notably similar to those measured in our study. That basin belongs to the Iberian Pyrite belt, one of the main metallogenic provinces in Europe, where pyrite and other sulphide ores have been exploited for centuries.…”
Section: Source: Pb Isotopic Signaturesupporting
confidence: 74%
See 1 more Smart Citation
“…a common predominant Pb origin (s) for all the samples (see Table 4). Therefore, average values were used to establish comparisons with possible sources; in this regard, Adánez et al (2015) have recently reported Pb isotopic ratios in samples of the Odiel-Tinto basin in the SW of Spain that are notably similar to those measured in our study. That basin belongs to the Iberian Pyrite belt, one of the main metallogenic provinces in Europe, where pyrite and other sulphide ores have been exploited for centuries.…”
Section: Source: Pb Isotopic Signaturesupporting
confidence: 74%
“…a Average of the 20 soil composite samples. b Data corresponding to the maximum highest Pb concentration within the 20 samples (4548 ppm).c Ranges obtained byAdánez et al (2015). dMarcoux (1998).…”
mentioning
confidence: 99%